(3cJGH KGhPhSjhS aj GdeSGcfs - (3KGhPhSjhSs
(3ChdgG (B:s
(3GdPjf eSGcfge JMJ GdbWH GdTeGdi aGf fUa cQI Gdcd GdXGgQ dge CHOkG XGgQ dge s
(3BNQgG (B:s
(3GdefbdH GdUjai KGdKjf jhekG hjXgQ dfG Cf HGbi GdfgGQ Edi HGbi Gddjd Ydi fSHI cd SfI hPdc eG CQOfG Cf fHjf Je cJGH KGhPhSjhS ai GdeSGcf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHYs
(3cJHJ Hbde eged GdfbXs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1458s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Gdadcs